Implementasi model pembelajaran berbasis proyek dalam meningkatkan keterampilan spasial siswa kelas xi ma bilingual batu melalui media simulasi bencana tanah longsor berbahan kardus - Syafaat, Mohamad Hisyam (Maliki Interdisciplinary Journal, 2025)
This study aims to improve the spatial skills of 11th grade students of MA Bilingual Batu through the implementation of project-based learning (PjBL) model by utilizing simulated landslide disaster media made from cardboard. The background of this research is the lack of students' spatial skills which are crucial in understanding geography concepts and disaster mitigation, as well as the lack of interesting learning media innovations. This Classroom Action Research (PTK) was conducted in two cycles, with each cycle including planning, implementation, observation, and reflection. The research subjects were students of class XI MA Bilingual Batu. Data were collected through participatory observation, spatial skills tests, and documentation. Data analysis was carried out quantitatively and qualitatively descriptive. The results showed a significant improvement in students' spatial skills after the implementation of PjBL using simulation media. In cycle I, the percentage of spatial skills completeness reached 56% (percentage obtained from evaluation results), and increased to 80% (percentage obtained from evaluation results) in cycle II. This increase was supported by students' enthusiasm in designing and creating simulation models, their ability to identify potential hazards, and a better understanding of disaster mitigation. Thus, it can be concluded that the project-based learning model with simulation media of landslide disaster made from cardboard is effective in mitigating disaster.